Auditoría operativa y su incidencia en el área administrativa de la compañía de transporte de carga pesada “Lamanence S.A” del cantón La Maná, provincia de Cotopaxi, periodo 2022. - Maldonado Cuenca, Mariuxi Elizabeth (2023)
The present project was directed to the execution of an operational audit through which it was possible to know the current situation of the administrative area of the company, the reason why this evaluation was carried out is to evaluate the incidence in the administrative department and generate recommendations for the improvement in the operations of the operational area. To give fulfillment of the research project has required the use of the types of research such as: bibliographic, field and descriptive research, in this way the research methods had a notable role in the advancement of knowledge in the field of study; that is why the inductive and deductive method was specified, in almost last instance the research techniques that were applied to complement; the interview, survey, observation, jointly with the research instruments such as: observation guide, control questionnaire, population and sample with which to work to know data of importance for the outcome of the evaluation. The main part of the audit is the elaboration of the working papers that support the function that was carried out, therefore, the programs of the evaluation of each one of the phases of the same one are exposed, as well as the activities that have been developed to detail the situation of the company. It is worth mentioning that during the planning phase, an interview with the manager was conducted, followed by a survey of the corporate partners and a SWOT matrix. Another factor that was evaluated was the internal control system through COSO I, in which the risk and confidence matrix was materialized, together with the internal control components, with the purpose of identifying the strengths and weaknesses present in the existing control system, The same resulted in some findings, which are detailed in the worksheets accompanied by the audit standard, where the control risk was determined in the control environment component at 20%, risk assessment at 30%, control activities at 0%, information and communication at 0%, supervision and monitoring at 0%, resulting in a total average of 10% in the determination of risk. On the other hand, the inherent risk detected in the entity is 5%, which reflects a low risk; however, it is important to develop strategies to prevent risks in future processes. Based on the findings found, conclusions and recommendations were issued according to the aspects studied, which were addressed to the manager and partners of the heavy cargo transportation company "Lamanence S.A.", for the proper follow-up and monitoring of the suggestions made, which will contribute to the improvement of the department. It is necessary to mention that the opinion issued in the internal control report and the audit report is duly supported by the competent ISA and in accordance with the provisions of the International Standards on Auditing.